Molecular detection of bacteria in dentinal carious lesions and in biofilm of children with different stages of early childhood caries - Beatriz GonÃalves Neves (2014)
Early childhood caries (ECC) is considered a serious public health issue among children all over the world. However, many aspects should be explored about the oral microbiota related to the ECC progression and how the bacterial community modifies according to the dentine lesion activity. This thesis, composed by two chapters, aimed to investigate and quantify with quantitative polymerase chain reaction (qPCR) the following bacteria Actinomyces naeslundii, Bifidobacterium spp., Lactobacillus acidophilus, Streptococcus gordonii, Streptococcus mutans, as well as members of the groups Lactobacillus casei and Mitis on biofilm from pre-school children with different stages of early childhood caries progression (Chapter 1) and on active and inactive dentine carious lesions (Chapter 2), and also to verify the association of these microorganisms on the process of health or disease. The sample consisted on preschool children aged between 2 and 5 years from nurseries and public preeschools in Fortaleza-CE. The children were examined for caries diagnosis with ICDAS II index (International Caries Detection Assessment System), and the Nyvad criteria, in order to evaluate prevalence and caries activity. The supragingival biofilm collection was taken from 75 children, who were divided in three groups according to the ICDAS II: CF (caries free) (n=20), ECL (presence of enamel caries lesion) (n=17) and DCL (presence of dentine caries lesion) (n=38). Samples of carious dentine were collected under rubber dam isolation of 56 lesions of dentine affected by caries, being 17 inactive and 39 active. The DNA of all the collected samples was extracted and purified, then tested for the presence of the formerly mentioned bacterial species/groups through qPCR. The quantity of bacteria was compared through the Kruskal-Wallis and Mann-Whitney tests. Besides, the association between the presence of bacteria and ECC was analyzed through the Chi-square test, with a 5% significance level and the multiple logistic regression was applied. Bacteria from the group L. casei and L. acidophilus presented low detection on biofilm of all evaluated groups. The presence of S. mutans and Bifidobacterium spp. showed a strong association with dental caries progression on the biofilm from children with dentine lesions with odds ratio of 21,5 and 5,9; respectively. On active dentine lesions, concentrations of Bifidobacterium spp. and species from the Lactobacillus casei group were significantly higher when compared to the inactive lesions (p<0.05). The levels of Actinomyces naeslundii, Streptococcus gordonni and species from Mitis group were not significantly different among biofilm groups as well as comparing dentine lesions. In conclusion, the microbial profile from biofilm samples presented differences on the proportion of acidogenic and aciduric bacteria with dental caries progression. The presence of Bifidobacterium spp. and S. mutans presented a strong association with the development of the more advanced stages of ECC. Regarding the activity of dentine lesions, higher detection levels of the group L. casei and Bifidobacterium spp. showed an important role of these bacteria in the dentine caries activity.